Exosome-Integrated Hydrogels for Bone Tissue Engineering - Hee Sook Hwang; Chung-Sung Lee (Gels)
Exosome-integrated hydrogels represent a promising frontier in bone tissue engineering, leveraging the unique biological properties of exosomes to enhance the regenerative capabilities of hydrogels. Exosomes, as naturally occurring extracellular vesicles, carry a diverse array of bioactive molecules that play critical roles in intercellular communication and tissue regeneration. When combined with hydrogels, these exosomes can be spatiotemporally delivered to target sites, offering a controlled and sustained release of therapeutic agents. This review aims to provide a comprehensive overview of the recent advancements in the development, engineering, and application of exosome-integrated hydrogels for bone tissue engineering, highlighting their potential to overcome current challenges in tissue regeneration. Furthermore, the review explores the mechanistic pathways by which exosomes embedded within hydrogels facilitate bone repair, encompassing the regulation of inflammatory pathways, enhancement of angiogenic processes, and induction of osteogenic differentiation. Finally, the review addresses the existing challenges, such as scalability, reproducibility, and regulatory considerations, while also suggesting future directions for research in this rapidly evolving field. Thus, we hope this review contributes to advancing the development of next-generation biomaterials that synergistically integrate exosome and hydrogel technologies, thereby enhancing the efficacy of bone tissue regeneration.